Photocatalytic air purification mimicking the self-cleaning process of the atmosphere - Fei He (Nature Portfolio, 2021)
Photocatalytic air purification is a promising technology that mimics nature’s photochemical process, but its practical applications are still limited despite considerable research efforts in recent decades. Here, we briefly discuss the progress and challenges associated with this technology.